Photosensitive field emission study of SnS2 nanosheets - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (Journal of Vacuum Science & Technology B, 2015)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to field emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solutions are used. The FE study is carried out in a planar diode configuration at a base pressure of similar to 10(-8) mbar. The emission photosensitivity is also investigated by illuminating the specimen with a visible light source. In dark, the turn on field, the electric field required to obtain a current density of 1 mu A/cm(2), is found to be 5.9 V/mu m. Upon illumination, the emitter with visible light, it is found to reduce to 5.0 V/mu m. A significant change in the nature of the Fowler-Nordheim plot with light illumination is also observed and has been explained on the basis of photoconductivity. Repetitive switching ON and OFF the light source, at a fixed applied voltage, is found to generate current pulses. The photosensitivity is also studied with various color filters. With the photoswitching and the enhanced field emission properties, it is envisaged that SnS(2)NSs possess a potential for optoelectronic applications of field emitters. (C) 2014 American Vacuum Society.